Termografia infravermelha na avaliação do carpo de bezerros da raça Holandesa - Borges, Pedro Augusto Cordeiro (2019)
For consolidate new diagnostic tools in bovine medicine this work aimed to standardize a methodology and reference values for thermographic evaluation of Holstein calves carpus. In a first study, carpal thermographic images of eight calves, obtained in a single moment, were analyze by GRAYESS® IRT Analyzer 7 software through global temperature (Ttot), region of interest (ROI) and mean maximum temperature (Tmax) methods. Tmax method was more effective than ROI and Ttot, to identify temperature differences between contralateral carpus, and possibly it’s the most applicable to diagnosis carpal joint diseases. Furthermore in this step of study, the temperature difference between contralateral carpus varied in a confidence interval of 0,03 to 0,26ºC, indicating that variations in this range, between contralateral carpus, can be normal. In a second study, thermographic images were obtained in five different moments (M1 = 31ºC, M2 = 29ºC, M3 = 27ºC, M4 = 26ºC, M5 = 14ºC) and through Flir Tools® the maximum temperatures of each carpi were summarized. A moderate positive correlation with carpal temperatures and a moderate negative correlation with the temperature difference between the right and left carpus of the same animal observed in relation to ambient temperature. At a later stage, a mathematic model applied to data to adjust environment temperatures to the same value. The model showed ability to reduce the influence of ambient temperatures on carpal temperatures, thus having potential to use in future experiments.